STUDY OF INITIAL MATERIAL FOR THE MAIZE BREEDING OF FOOD AND TECHNICAL APPLICATION IN THE USTIMOVSKAYA CROP RESEARCH STATION - Харченко, Ю. В.; Харченко, Л. Я.; Тимчук, С. М.; Поздняков, В. В.; Супрун, О. Г. (Scientific Progress & Innovations, 2014)
The wide variability of the maize inbreeds – carriers of different endospermic mutations for the grain productivity, content and fractional composition of starch as well as the content of oil and oleic acid glycosides were established. It is shown that the improvement of maize for these indicators requires the use of a wide genetic diversity of crops and quality of the source material. It have been determined the effects of combining ability of the inbreeds – carriers of mutations wx, su2,ae, su1 and sh2 for these traits. The perspective initial material for the maize breeding of food and technical application was identified.